2010
DOI: 10.1108/01409171011065608
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of wealth on merger announcements in India

Abstract: Purpose -Research on mergers has made considerable progress over the last 50 years and has produced a vast body of literature, especially in the developed markets of the world. Little is known about the effect of announcements of mergers on shareholder wealth in the Indian context. Also unknown is the apparent influence of the market for corporate control on such wealth effects. The purpose of this paper is to fill gaps in this knowledge. Design/methodology/approach -The study uses a standard event study metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…These findings are in sync with the results drawn by [11][12][13][14]16] and contrast with the findings.…”
Section: Fig 3 Cumulative Average Abnormal Returns During the Event W...supporting
confidence: 60%
See 1 more Smart Citation
“…These findings are in sync with the results drawn by [11][12][13][14]16] and contrast with the findings.…”
Section: Fig 3 Cumulative Average Abnormal Returns During the Event W...supporting
confidence: 60%
“…Reference [12] examined the merger announcement impact on the wealth of shareholders of the acquiring firm, acquired firm and combined firm. The findings of the study using the 34 firms conclude that shareholder of the acquiring firm earns 11.6% in an event window of 21 days.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that shareholder's wealth declined when the securities were more prone to market risk, and when the market risk of the public and private sector banks were same as that of the benchmark portfolio, there was an increase in the shareholder's wealth. Ramakrishnan (2010) in his study with respect to companies listed in BSE, found that on an average, only the shareholders of the acquired firm appear to enjoy significant wealth gains. Ghosh and Dutta (2015) analysis the M&As undertaken in the BFSI sector using certain ratios.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Kumar and Suhas (2010) opined that mergers created value for the acquirer banks but eroded shareholder wealth for target firms. Ramakrishnan (2010) who researched on the effect of announcements of mergers on shareholder wealth in the Indian context concluded that the acquired firms' shareholders enjoyed significant wealth gains whereas the acquiring firms' shareholders did not experience the same. Ravichandran et.…”
Section: Studies On Stock Market Performance Measuresmentioning
confidence: 99%